Pengaruh beberapa indeks saham global dan indikator makroekonomi terhadap pergerakan IHSG - Dian Oktarina (Journal of Business & Banking, 2015)
In 2007, the financial crisis occurred in the USA and in 2008-2009, it caused the Jakarta Composite Index (JCI) to decline which led to the fall of the Dow Jones Index. This eco-nomic condition affected all of the countries including Indonesia, as well as without ex-ception the capital markets industries. This study is mainly to determine the effect of several global stock indices and macroeconomic indicators on JCI. The global stock indic-es and macroeconomic indicators used in this study are: the Dow Jones Industrial Aver-age Index, Nikkei 225 index, Shanghai Composite Index, FTSE100 index, oil prices, gold prices, exchange rate IDR/USD, BI rate, and inflation, that were taken monthly from 2009 until 2014. This research used multiple linear regression analysis. The result indi-cates that the Dow Jones Industrial Average index, Nikkei 225 index, gold prices, and inflation give the positive effect to JCI, while Shanghai Composite index, FTSE100 index, oil prices, exchange rate IDR/USD, and BI rate give the negative effect to JCI. The next research can add some variable index of Asia Pacific countries such as: Hang Seng Index, Kospi Index, BSE index and macroeconomic indicator variables such as GDP.